Editorial: New Generation Therapeutic Modalities - Peter Timmins (University of Huddersfield Press, 2018)
I spend quite a bit of time collating information from pharmaceutical company press releases and news feeds to compile review articles describing the latest advances in therapeutic approaches (novel targets, growth in options for treatment of rare diseases, emerging modalities such as CAR-T, new drug delivery technologies, etc.). Based on what I have seen over the last few years, looking at the evolution in this space, I sense there may be potential impacts for pharmacy we ought to consider, if we are not already doing so, for the profession and the science of pharmacy and in the education and training of future pharmacists and pharmaceutical scientists. My most recent review of information showed that a significant amount of new research collaborations involving pharmaceutical companies and of early phase clinical research highlighted gene delivery, oligonucleotide therapeutics, CAR-T therapeutics, and novel treatments for rare diseases.